Micromorphology of Quaternary Calcretes around Didwana in Thar Desert of Rajasthan - Achyuthan, Hema; Rajaguru, S N (Annals of Arid Zone, 2016)
Quaternary calcretes within the dunes and interdune pan deposits around Didwana have been classified on the basis of their field occurrences, morphology, microtexture and microfeatures. Micromorphological analyses helped to understand the development of these calcretes. The study reveals that ’the calcium carbonate nodules in the lower horizons of the dune profiles, and in the interdune pans have been formed by the complex process of pedogenesis and ground water action in semi-arid to arid climate.